NEK1 Variants in a Cohort of Italian Patients With Amyotrophic Lateral Sclerosis - Riva, Nilo; Pozzi, Laura; Russo, Tommaso; Pipitone, Giovanni Battista; Schito, Paride; Domi, Teuta; Agosta, Federica; Quattrini, Angelo; Carrera, Paola; Filippi, Massimo (Frontiers in Neuroscience, 2022)
Introduction: In the last few years, different studies highlighted a significant enrichment of NEK1 loss of function (LoF) variants in amyotrophic lateral sclerosis (ALS), as well as an additional role for the p.Arg261His missense variant in the disease susceptibility. Several other missense variants have been described so far, whose pathogenic relevance remains however unclear, since many of them have been reported in both patients and controls. The aim of our work was to investigate the presence of NEK1 variants and their correlation with phenotype in a cohort of Italian ALS patients. Methods: We sequenced a cohort of 350 unrelated Italian ALS patients by Next Generation Sequencing (NGS) and then we analyzed the clinical features of NEK1 carriers. Results: We detected 20 different NEK1 rare variants (four LoF and 16 missense) in 33 unrelated patients with sporadic ALS (sALS). The four LoF variants (two frameshift and two splice-site variants) were all novel. The p.Arg261His missense variant was enriched in patients’ cohort (p<0.001). Excluding this variant from counting, the difference in the frequency of NEK1 rare missense variants between patients and controls was not statistically significant. NEK1 carriers had a higher frequency of flail arm (FA) phenotype compared with the other patients of the cohort (29.2% vs 6.4%). Nine NEK1 carriers (37.5%) also harbored variants in other ALS-related genes. Conclusions: Our study confirms that NEK1 LoF and p.Arg261His missense variants are associated with ALS in an Italian ALS cohort and suggests a correlation between the presence of NEK1 variants and FA phenotype.